OPTIMIZING HUMAN-AI INTERACTION: ARTIFICIAL EMPATHY STRATEGIES IN ENHANCING AFFECTIVE AND SOCIAL CUSTOMER EXPERIENCES - Paramarta, Vip; Kosasih; Aripin, Zaenal (Organisasi Kreatif Indonesia Emas, 2024)
Human-AI interaction has become an important focus in the development of more responsive and humane technology. In this context, the use of artificial empathy strategies is of particular interest due to its potential in improving customer experiences affectively and socially. This research aims to explore the optimization of human-AI interactions through the application of artificial empathy strategies in improving affective and social customer experiences. The research approach used is qualitative by reviewing various studies and related literature. The data sources used are journals, articles and books that are relevant to the research topic. From the research results, it was found that the implementation of artificial empathy strategies in human-AI interactions has great potential to improve the quality of interactions and customer experiences. The use of technologies such as natural language processing, emotion recognition, and sentiment analysis can enable AI to respond more precisely and sensitively to user needs and emotions.